Enhancement of Power Consumption of Tasks Scheduling Algorithms on a Multi-Core Platform in Real Time Systems - حجازية محمد; نتيفة يوسف (Latakia University Journal -Engineering Sciences Series, 2022)
Real-time systems are the basic core of most research fields in both academic and applied directions, and the reason for this is due to the need to provide a high quality of service for these fields as a result of the rapid and increasing progress of information and communication technology, in addition to the rapid development in the design of processors and electronic controllers, which have high processing speed and the ability to Communicate with a very wide range of other peripheral units. The basic core in the success of any system that works in real time is its possession of an accurate and tight scheduling algorithm capable of dealing with various types of tasks, such as periodic, sporadic and aperiodic, where the effectiveness of the algorithm lies in ensuring the execution of these tasks in a logical manner without exceeding the associated time constraints. Recently, researchers have tended to study the possibility of the real-time system working in power-saving conditions due to the large spread of portable devices and the dependence of these devices in their work on real-time systems, and this research aims to provide development and improvement on the work of scheduling algorithms in terms of energy consumption during the operation of the system. In this research, an integrated software system for the LLREF scheduling algorithm was designed and built using the MATLAB integrated development environment, based on the mathematical model of each of the algorithm, tasks, multi-core platform and energy consumption equations.